Precautions for Pneumo-Orbital in Cases of Maxillofacial Trauma: Data Mining for Artificial Inteligence of Air Localization on CT-Scan - Karla Kalua; Muchtar Hanafi; Rachmi Fauziah Rahayu (Universitas Sebelas Maret, 2023)
Along with rapid mobility, the incidence of traffic accidents is increasing. Maxillofacial trauma often accompanies traffic accidents. Facial bone fractures need serious concern, considering that the face contains several important organs and an important aesthetic aspect daily. Pneumo-orbital, in which air is found in the orbital cavity, is a threat to vision. The development of diagnostic modalities for maxillofacial trauma is developed continuously for determining the accuracy and improving rapid diagnosis. A radiologist is greatly facilitated by the presence of a CT scan that is able to detect certain abnormalities through artificial intelligence (AI) features. The data of this study are preliminary data showing the incidence of pneumo-orbital that was often missed in maxillofacial trauma cases. The maxillofacial trauma cases (classified as Le Fort fractures) were collected from January 2022 to July 2022 consecutively and determined into Le Fort fractures with pneumo-orbital and without pneumo-orbital. From 19 cases, 13 cases (68%) were accompanied by pneumo-orbital, while 6 cases (32%) were not. Multiple pneumo-orbitals with relatively visible sizes are detected easily on CT scan but a single and relatively small pneumo-orbital has potentially not to be seen on CT scan. It is concluded that CT scan nowadays is not only used to see anatomical abnormalities, but also equipped with AI-based features; such as the intracranial bleeding volume calculation and calcium score estimation on cardiac CT. It is possible that a CT scan can also detect the presence of air particles. Thus, the sensitivity of pneumo-orbital detection can be increased.